Розробка системи наведення і стабілізації з нейрорегулятором на основі моделі авторегресії з ковзним середнім - Кузнецов, Б.І.; Василець, Т.Ю.; Варфоломієв, О.О. (Електротехніка і електромеханіка, 2011)
Synthesis of a light-armored vehicle armament guidance and stabilization system is performed with application of a neurocontroller on the basis of an autoregressive moving average model. The neuro-controller architecture and principle of operation are presented. A schematic model of the guidance and stabilization system with a proportional controller in the position loop and a neuro-controller in the speed loop is developed. NARMA-L2 controller is synthesized. Computer simulation is made, the system dynamic behavior analyzed.